INTERNAL CONTROL ON MILITARY ASSETS ACCORDING TO MILK AL-DAULAH IN ISLAMIC ECONOMIC LAW: A STUDY IN KUTA ALAM DORMITORY BANDA ACEH, INDONESIA - Wilda Nadhiratul Safira; Zulhamdi (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
This article aims to examine the internal control system of national military assets in Indonesia at the Kuta Alam Banda Aceh barracks, reviewed according to the concept of milk al-daulah. The approach taken by the author is a juridical-empirical study. The research findings indicate that to address issues in the internal control system of assets in the Indonesian National Army (TNI) at the Kuta Alam Banda Aceh barracks, a holistic approach is required to effectively tackle existing challenges. It is crucial to update and refine the inventory process to ensure that asset data is more accurate and current. Implementing an integrated, technology-based asset management system will facilitate tracking and monitoring. Furthermore, asset maintenance should be scheduled regularly and its implementation should be ensured to prevent damage that could increase repair costs. Enhancements in surveillance technology, such as modern CCTV and access control systems, are essential to reduce the risk of theft and damage. Compliance with policies should be strengthened through intensive training and consistent enforcement to ensure procedures are properly followed. Risk management also needs improvement with more effective and proactive mitigation strategies. Additionally, the use of advanced technology can support efficiency in asset management and reporting. Transparency should be increased by providing clear and accessible reporting mechanisms, while budget management should be improved to ensure efficient allocation. Regular personnel training is important to keep their skills relevant, and routine audits and evaluations should be conducted to maintain the effectiveness of the internal control system.